2013
DOI: 10.1002/jts.21823
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Coping Style and PTSD on Family Functioning After Deployment in Operation Desert Shield/Storm Returnees

Abstract: The relationship between military combat and postdeployment family functioning difficulties has been frequently investigated in the literature, as has the relationship between types of coping and posttraumatic stress disorder (PTSD). Few studies, however, have examined these variables together, and no studies of which we are aware have examined the effect of coping on family functioning after combat exposure. This study examined coping style measured immediately after return from deployment, and PTSD symptoms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 25 publications
3
14
0
Order By: Relevance
“…Creech et al suggested that the strategies used to cope with combat stress may impact both PTSD and the functionality of the family. Moreover, it can highlight the potential utility of pre- and post-deployment coping skills training ( 25 ). Renshaw and Caska performed a study to investigate the role of partners’ perceptions of post-traumatic stress symptom.…”
Section: Discussionmentioning
confidence: 99%
“…Creech et al suggested that the strategies used to cope with combat stress may impact both PTSD and the functionality of the family. Moreover, it can highlight the potential utility of pre- and post-deployment coping skills training ( 25 ). Renshaw and Caska performed a study to investigate the role of partners’ perceptions of post-traumatic stress symptom.…”
Section: Discussionmentioning
confidence: 99%
“…Oseland et al (2016) have indicated these components are mutually influential components of the couple relationship. The revisions to the CATS Model are based on previous research on couples and trauma since the 2005 model was published (See Campbell & Renshaw, 2011Creech et al, 2013;Henry et al, 2011;Monk & Nelson Goff, 2014;Nelson Goff et al, 2007, 2009, 2015Renshaw, Rodrigues, & Jones, 2008, 2009Taft et al, 2011;Wick & Nelson Goff, 2014). While the CATS Model provides a systemic description of the individual and relational effects of trauma, more research is needed to further understand the relationship between individual and relationship functioning and disclosure of prior trauma experiences, particularly in veteran couples.…”
Section: The Couple Adaptation To Traumatic Stress (Cats) Modelmentioning
confidence: 99%
“…Looking at the couple level, there is preliminary work indicating disclosure may have a buffering effect for relationship adjustment for those below the clinical threshold for PTSD (Monk & Nelson Goff, 2014). Researchers have found that relationships can be negatively affected even when there is avoidance of directly discussing trauma experiences (e.g., Creech et al, 2013;Nelson Goff et al, 2006). Communication between spouses has been found to be an important component for relationship functioning in trauma survivors (Nelson Goff et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…114,115 PTSD has been associated with aggression/violent behavior, marital difficulties, partner distress, lower parental functioning, and increased behavioral issues among the children of Veterans with PTSD. 116 When examining how PTSD impacts the family, one study found that the method of coping with symptoms used by Veterans predicted family functioning.…”
Section: For Further Information)mentioning
confidence: 99%
“…Specifically, an avoidant coping style was associated with greater family dysfunction as compared with an approach coping style. 114 Fortunately, there are several avenues of support for family, in the form of crisis services (eg, Veterans Crisis Line, National Domestic Violence Hotline, National Child Abuse Hotline, VA Caregiver Support Line) as well as supportive and preventative health services (eg, VA Caregiver Support, Coaching Into Care Program, National Resource Directory, Vet Center Combat Call Center). In addition, several studies have demonstrated positive effects of couples and family therapy.…”
Section: For Further Information)mentioning
confidence: 99%